Use of surface electromyography in phonation studies: an integrative review - Silva,Hilton Justino da (2013)
INTRODUCTION: Surface electromyography has been used to assess the extrinsic laryngeal muscles during chewing and swallowing, but there have been few studies assessing these muscles during phonation. OBJECTIVE: To investigate the current state of knowledge regarding the use of surface electromyography for evaluation of the electrical activity of the extrinsic muscles of the larynx during phonation by means of an integrative review. METHOD: We searched for articles and other papers in the PubMed, Medline/Bireme, and Scielo databases that were published between 1980 and 2012, by using the following descriptors: surface electromyography and voice, surface electromyography and phonation, and surface electromyography and dysphonia. The articles were selectedon the basis ofinclusion and exclusion criteria. DATA SYNTHESIS: This was carried out with a cross critical matrix. We selected 27 papers,i.e., 24 articles and 3 theses. The studies differed methodologically with regards to sample size and investigation techniques, making it difficult to compare them, but showed differences in electrical activity between the studied groups (dysphonicsubjects, non-dysphonicsubjects, singers, and others). CONCLUSION: Electromyography has clinical applicability when technical precautions with respect to application and analysis are obeyed. However, it is necessary to adopt a universal system of assessment tasks and related measurement techniques to allow comparisons between studies.